Effects of six weeks of beta-hydroxy-beta-methylbutyrate (HMB) and HMB/creatine supplementation on strength, power, and anthropometry of highly trained athletes - O'Connor, D. M.; Crowe, M. J. (The Journal of Strength and Conditioning Research, 2007)
This study investigated the effects of 6 weeks of dietary supplementation of [beta]-hydroxy-[beta]-methylbutyrate (HMB) and HMB combined with creatine monohydrate (HMBCr) on the muscular strength and endurance, leg power, and anthropometry of elite male rugby league players. The subjects were divided into a control group (n = 8), a HMB group (n = 11; 3 g[middle dot]d-1)or a HMBCr group (n = 11; 12 g/d with 3 g HMB, 3 g Cr, 6 g carbohydrates). Three repetition maximum lifts on bench press, deadlifts, prone row, and shoulder press, maximum chin-up repetitions, 10-second maximal cycle test, body mass, girths, and sum of skinfolds were assessed pre-and postsupplementation. Statistical analysis revealed no effect of HMB or HMBCr on any parameter compared with presupplementation measures or the control group. HMB and HMBCr were concluded to have no ergogenic effect on muscular strength and endurance, leg power, or anthropometry when taken orally by highly trained male athletes over 6 weeks.